2009
DOI: 10.1002/chem.200901238
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Reactivities of Iron(IV)‐Oxo Porphyrin π‐Cation Radicals in Oxygenation Reactions by Electron‐Donating Axial Ligands

Abstract: The proximal axial ligand in heme iron enzymes plays an important role in tuning the reactivities of iron(IV)-oxo porphyrin pi-cation radicals in oxidation reactions. The present study reports the effects of axial ligands in olefin epoxidation, aromatic hydroxylation, alcohol oxidation, and alkane hydroxylation, by [(tmp)(+*) Fe(IV)(O)(p-Y-PyO)](+) (1-Y) (tmp = meso-tetramesitylporphyrin, p-Y-PyO = para-substituted pyridine N-oxides, and Y = OCH(3), CH(3), H, Cl). In all of the oxidation reactions, the reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
141
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(160 citation statements)
references
References 76 publications
16
141
3
Order By: Relevance
“…An explanation for the rate acceleration could therefore simply be an enhanced stabilization of the high-valent species. The same trend is also observed for iron porphyrins [111] as covered in the next section.…”
Section: (A) Examples Of Nonheme Iron(iv)-oxo Complexes (B) Preparatsupporting
confidence: 77%
See 1 more Smart Citation
“…An explanation for the rate acceleration could therefore simply be an enhanced stabilization of the high-valent species. The same trend is also observed for iron porphyrins [111] as covered in the next section.…”
Section: (A) Examples Of Nonheme Iron(iv)-oxo Complexes (B) Preparatsupporting
confidence: 77%
“…Generally, it has been observed that oxidative power increases when the porphyrinic scaffold is decorated with electron-withdrawing substituents [117,118]. Somewhat counterintuitively, it has also been shown that the reactivity of [Fe IV O(TMP)( p-OPyY)] + complexes towards the electrophilic epoxidation of olefins and hydroxylation of aromatic and aliphatic substrates increases, when Y is an electron-donating group [111]. DFT calculations indicate that a complicated transeffect is at play.…”
Section: Iron(v)oxo and Iron(iv)oxo-(oxidized Radical Ligand) Complexesmentioning
confidence: 94%
“…The axial ligands bound trans to the iron-oxo moiety also markedly influence the reactivities of oxoiron(IV) porphyrin π-cation radicals. For example, a recent study by Kang et al 30 (Fig. 5a) and theoretical methods, showed that rates of both the O-transfer and H-atom abstraction reactions of the porphyrin Figure 2 | Reactions catalysed by high-valent oxo intermediates of iron-containing enzymes.…”
mentioning
confidence: 99%
“…[4a,8c, 13,24] In particular, it was shown that N-donor ligands such as imidazole derivatives play a key role in Mn-porphyrin-or Mn-salen-catalyzed olefin epoxidations by H 2 O 2 . We tested the influence of a variety of additives on the styrene epoxidation catalyzed by complex 2 with H 2 O 2 in acetonitrile, by comparing the conversion into styrene oxide obtained after 90 min in the presence and in the absence of the additive.…”
Section: Epoxidation Of Olefins Catalyzed By the Manganese Complexmentioning
confidence: 99%